Education for Sustainable Development (ESD) in Science Learning: A Systematic Literature Review on the Benefits and Commonly Addressed Sustainability Goals - Nida Sayyidah Munawar; Diana Rochintaniawati; Nanang Winarno; Rika Rafikah Agustin; Eliyawati Eliyawati (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study aims to analyze 40 Scopus-indexed articles from 2015-2025 related to Education for Sustainable Development (ESD) in science learning. This study employs PRISMA and the systematic literature review method. The results of this study show that the most articles found were published in 2015 and 2021, with 7 articles each. Most articles came from Germany (8 articles). The research method that is often used is mixed methods (15 articles), with the most research objects being undergraduate students (16 articles), and mostly covering science material (19 articles). The most applied research benefit in the research is integrating three ESD domains, namely cognitive, socio-emotional, and behavioral. The SDGs that are most commonly mentioned in the studied literature are SDG 4 (Quality Education), SDG 13 (Climate Action), and SDG 12 (Responsible Consumption and Production). The findings in this study can offer a thorough summary that can be used to create science education plans that incorporate ESD principles, as well as become recommendations for further research related to ESD in science learning.